Discovery of SIPI6473, a New, Potent, and Orally Bioavailable Multikinase Inhibitor for the Treatment of Non-small Cell Lung Cancer - Xiu Gu; Zi-Xue Zhang; Min-Ru Jiao; Xin-Yan Peng; Jian-Qi Li; Qing-Wei Zhang (Georg Thieme Verlag KG, 2021)
Abstract A novel series of quinazoline derivatives were designed, synthesized, and evaluated as multikinase inhibitors. Most of these compounds showed antiproliferation activities of several human cancer cell lines and exhibited inhibition efficacy against the estimated glomerular filtration rate (EGFR) in the nanomolar level. Among those compounds, compound B5 (also named SIPI6473) displayed the maximum effect, and thus was chosen for further study. Our data revealed that B5 inhibited the activity of several kinases (such as EGFR, VEGFR2, and PDGFRα) that contributed to the development of non-small cell lung cancer (NSCLC). Besides, an in vivo study also showed that B5 inhibited tumor growth without signs of adverse effects in the A549 xenograft model. In conclusion, B5 may represent a new and promising drug for the treatment of NSCLC.